Alternative design approach for energy management system - R. Roadprasert (2018)
Energy Management System (EMS) is introduced in order to help the governing body and the utility itself to perform the most suitable decision making activities at the right time. Many EMS design approaches have been developed, though only focusing on each utility. This usually results in the fragmentation and in many cases, the duplication of the EMS, not being able to support ESI as a whole. This paper proposes an alternative design approach for an EMS based on the top-down approach. The national electricity industry framework has been developed using the application of balance scorecard. This is to define the overall required tasks within the ESI, which could then be assigned to different entities. Knowledge Engineering, especially the communication model, is then utilized to construct the knowledge and information exchange protocol between and within entity. Finally, the Common Information Model (CIM) can be developed for the EMS. In this paper, the Thai ESI was used as a case study. The results have shown that the alternative approach proposed in this research provides systematic framework for EMS design allowing the modification to the initial EMS when it is needed. Moreover, the approach can lead to the properly designed EMS with the convergence of data and information exchange among different entities which can then be effectively used by the governing body and regulator in decision making activities.